MODERN VIEWS ON CEREBRASTHENIC SYNDROME IN CHILDREN - Husainov Elur Doniyor Ugli; Primkulov Ramazon Rakhimkul Ugli; Kayumov Otabek Oybekovich; Toyirov Diyorbek Azamatovich; Kasimov Arslanbek Atabayevich; Mamurova Mavludakhon Mirkhamzayevna (Western European Studies, 2024)
Cerebrasthenic syndrome in children is a nonspecific neurological symptom complex caused by immaturity, delayed development of central mechanisms of nervous regulation. It is manifested by asthenia: increased fatigue, exhaustion of mental and physical activity, drowsiness, decreased concentration, irritability, headache. Diagnosis is based on clinical and neurological examination, supplemented by instrumental studies of the brain, psychological testing, laboratory analysis. Treatment is complex, including medication, physiotherapy and psychocorrection
Keywords: Cerebrasthenic syndrome; children; complex treatment